Bis(N-butyl-N-ethyldithiocarbamato-kappa S-2,S `)nickel(II) - Juhari, W.N.S.W.; Baba, I.; Farina, Y.; Ng, S.W. (International Union of Crystallography, 2010)
The dithiocarbamate anions in the title compound, [Ni(C7H14NS2)(2)], chelate to the Ni-II atom, which is four-coordinate in a square-planar geometry. The Ni-II atom lies on a center of inversion